2020
DOI: 10.3389/fpsyg.2020.01377
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Misconception About Deception and Nervous Behavior

Abstract: In this article, we attempt to unravel the misconception about deception and nervous behavior. First we will cite research demonstrating that observers believe lie tellers display more nervous behaviors than truth tellers; that observers pay attention to nervous behaviors when they attempt to detect deception; and that lie tellers actually feel more nervous than truth tellers. This is all in alignment with a lie detection approach based on spotting nervous behaviors. We then will argue that the next, vital, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…Looking for the nonverbal “hot spots” of individuals is very suitable for the scenario in which rapid evaluation is required. Some other approaches of deception detection, for example, brain activities, cannot provide real-time results (Vrij & Fisher, 2020). The results suggested that the “hot spots” - emotional expressions of fear - could distinguish between truthful and deceptive messages with a reasonable level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking for the nonverbal “hot spots” of individuals is very suitable for the scenario in which rapid evaluation is required. Some other approaches of deception detection, for example, brain activities, cannot provide real-time results (Vrij & Fisher, 2020). The results suggested that the “hot spots” - emotional expressions of fear - could distinguish between truthful and deceptive messages with a reasonable level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Looking for the nonverbal "hot spots" of individuals is very suitable for the scenario in which rapid evaluation is required. Some other approaches of deception detection, for example, brain activities, cannot provide real-time results (Vrij & Fisher, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given the need to suppress information during deception, deception researchers have investigated behavioral cues associated with reticent communication. People often assume that nervousness is a sign of deceptiveness even if objectively, that is untrue ( Vrij and Fisher, 2020 ). Although the proposition that deception can be revealed through shifty eyes has all but been disproven, cues associated with deception do overlap with ones associated with anxiety and nervousness.…”
Section: Hypothesesmentioning
confidence: 99%
“…Although this research does not necessarily align rigidity with nervousness, nervous behaviors are associated with rigidity, including kinesic cues ( Gregersen, 2005 ) and vocal tension ( Laukka et al, 2008 ). This is partly because deception is thought to increase cognitive load, and higher cognitive load reduces overall activation ( Vrij and Fisher, 2020 ). However, previous studies showed mixed results in the associations between vocal variations and nervousness.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation